Investigation of the Catalytic Activity of Hybrid Decavanadate Materials - DEAK, Noemi; IDBOUMLIK, Meryem; SORAN, Albert; LACHKAR, Mohammed Abdulhakim; EL BALI, Brahim; NEMES, Gabriela (Studia Universitatis Babeș-Bolyai Chemia, 2024)
Three decavanadate (V10O28)6- containing compounds were used to test their catalytic activity in the sulfoxidation reaction of diphenyl sulfide using environmentally friendly conditions (low temperature, non-toxic solvent). The compounds of interest for our study, (NH4)2(H2en)2V10O28·4H2O, (H2en)3V10O28·6H2O and {Li2(H2O)10}(V10O28)(NH4)4, were evaluated, showing good activity in sulfoxidation reaction and leading to complete conversion of the sulfide even after three runs. The tetraammonium decaaqualithium decavanadate, with the formula {Li2(H2O)10}(V10O28)(NH4)4 was obtained through a modified literature method and its structure re-determined and investigated, giving similar results as previously described and confirming the structure of the used material.